Factors Causing Anemia in Women of Reproductive Age - Putri Diana; Nur Hikmah (LPPM Universitas Duta Bangsa Surakarta, 2021)
The health problem that is still facing the world today is anemia. The incidence of anemia in the world currently reaches 9% in developed countries and about 43% in developing countries. One age group that is prone to suffer from anemia are women of childbearing age (WUS). WHO says that 35-75% of anemia in developing countries occurs in children and women of reproductive age. The factors that cause anemia in women of reproductive age are social, cultural and economic factors, as well as nutritional factors. This study aims to determine the factors that cause anemia in women of reproductive age. The research method used descriptive research with a total population of 56 and a sample of 49 women of reproductive age who suffered from anemia. The results of the study were 42.8% of respondents who suffered from anemia had a basic or low education, 51% of respondents with a low level of knowledge suffered from anemia, 55.1 % who suffer from anemia have a poor nutritional status and 85.7% of respondents who suffer from anemia have an unhealthy diet. So it can be concluded that the factors that cause anemia in women of reproductive age are the level of education, level of knowledge, nutritional status and diet.